Performance Evaluation of Multi-hop WirelessHART Network on a Real-life Testbed - Ghosh, Tirthankar; Worku, Kaleab; Hupp, Jacob; Zheng, Yi (Discoveries in Agriculture and Food Sciences, 2018)
Advances in WirelessHART standard in industrial control systems have led to performance evaluation and security analysis in both real-world testbeds as well as in controlled lab environments. We have conducted months-long experiments with WirelessHART network in a multi-hop setting in our laboratory. Latency, stability, and reliability have been used as metrics to measure performance of individual links and the overall network for five hops and seven hops. We have deliberately deviated from following the best practices in designing the topology to study network performance under strained conditions. In addition to using metrics as defined in WirelessHART literature, we have also studied network stability over multiple hops with single paths. Our findings show that having at least one low stability link can have an impact on multihop stability, while still maintaining a very high overall network reliability of 99.98% or higher. Details of the experiment along with results and lessons learned are presented in the paper.